Pengaruh Motivasi, Lingkungan Kerja Dan Kepemimpinan Terhadap Kinerja Karyawan Pada Karyawan Rumah Sakit Islam Malang Kota Malang - Andry, Andry; Widarko, Agus; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research discusses the crucial role of human resources in the sustainability of a company, particularly at Islamic Hospital Malang. The presence and quality of human resources have a significant impact on the formation and operation of the institution. The focus on patient care makes the role of human resources crucial in achieving the hospital's achievements and progress. This research aims to identify the influence of motivation, work environment, and leadership on employee performance in the hospital. Motivation serves as a driving factor for employees to achieve goals and enhance their performance. Additionally, a conducive work environment and effective leadership are also key factors in shaping individual and group performance. The assessment of employee performance is vital in evaluating the quality of individual and group work outcomes, measured based on operational standards and organizational goals.  Keywords: Human resources, Employee performance, Motivation, Work environment, Leadership, Hospital, Performance assessment, Achievement, Company sustainability.